Leadership and Technology: a bibliometric study in the Scientific Periodicals Electronic Library (2020-2022) (Research, Society and Development, 2022)
This article aims to develop a study on leadership in the technological scenario from a bibliometric study, between the years 2020 and 2022. It has a quantitative-descriptive approach, using as a basis a bibliometric study, developed on the basis of Scientific Periodicals Electronic Library (SPELL) data analysis, using the term: Leadership and Technology. It was identified, through an analysis, that there was an announcement of 40, the first being published in 2020 and the same articles presented in a number of elaborated studies (23). It is noteworthy that the production of studies follows an expansion with the evolution of the years, considering that the theme (Leadership and Technology) is a current term that continues to evolve, however, it is important that the number of articles is considered minimum importance and applicability of the object of study.